F n , F_n, but not Fibonacci

Let F n = 2 2 n + 1 F_n = 2^{2^n} + 1 for all nonnegative integers n . n. Find the maximum possible value of gcd ( 201 8 F a 1 , 201 8 F b 1 ) , \gcd \left(2018^{F_a} - 1,\ 2018^{F_b} - 1\right), where a , b a, b are distinct nonnegative integers.

Note: Input 1 -1 if you believe there is no maximum, i.e. the expression can be arbitrarily large.


The answer is 2017.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Steven Yuan
Mar 16, 2018

We will first prove these two lemmas:

Lemma 1: gcd ( a m 1 , a n 1 ) = a gcd ( m , n ) 1. \gcd(a^m - 1, a^n - 1) = a^{\gcd(m, n)} - 1.

Proof of Lemma 1: Let d = gcd ( a n 1 , a m 1 ) . d = \gcd(a^n - 1, a^m - 1). WLOG we can assume that m n . m \geq n. Thus, we can write m = n q 1 + r 1 , m = nq_1 + r_1, where q 1 , r 1 q_1, r_1 are integers with q 1 > 0 q_1 > 0 and 0 r 1 < n . 0 \leq r_1 < n. By the Euclidean Algorithm,

d = gcd ( a m 1 , a n 1 ) = gcd ( ( a m 1 ) ( a n q 1 1 ) , a n 1 ) = gcd ( a n ( a m n q 1 1 ) , a n 1 ) = gcd ( a r 1 1 , a n 1 ) . d = \gcd(a^m - 1, a^n - 1) = \gcd((a^m - 1) - (a^{nq_1}- 1), a^n - 1) = \gcd(a^n(a^{m - nq_1} - 1), a^n - 1) = \gcd(a^{r_1} - 1, a^n - 1).

Since n > r 1 , n > r_1, we can write n = q 2 r 1 + r 2 , n = q_2r_1 + r_2, so that by applying the Euclidean Algorithm again as shown above, we get d = gcd ( a r 2 1 , a r 1 1 ) . d = \gcd(a^{r_2} - 1, a^{r_1} - 1). Eventually, after repeating this process some number of times, we end up with r k 1 = q k + 1 r k r_{k - 1} = q_{k + 1}r_k so d = a r k 1. d = a^{r_k} - 1. But note that r k r_k is precisely the greatest common divisor of m m and n , n, because the process that we used to reduce the exponents is the Euclidean Algorithm applied to m , n . m, n. Thus, r k = gcd ( m , n ) , r_k = \gcd(m, n), and d = a gcd ( m , n ) 1. d = a^{\gcd(m, n)} - 1. \, \blacksquare

Lemma 2: If m n , m \neq n, then gcd ( F m , F n ) = 1. \gcd(F_m, F_n) = 1.

Proof of Lemma 2: For this proof, we utilize the identity

F n = F 0 F 1 F n 1 + 2. F_n = F_0 F_1 \cdots F_{n - 1} + 2.

This can be proven with induction: for n = 1 , n = 1, F 1 = 2 2 + 1 = 5 = 3 + 2 = F 0 + 2 , F_1 = 2^2 + 1 = 5 = 3 + 2 = F_0 + 2, and if it's true for n = k , n = k, then

F k + 1 = 2 2 k + 1 + 1 = ( 2 2 k ) 2 1 + 2 = ( 2 2 k 1 ) ( 2 2 k + 1 ) + 2 = F n ( F n 2 ) + 2 = F 0 F 1 F k + 2 , F_{k + 1} = 2^{2^{k + 1}} + 1 = \left ( 2^{2^k} \right )^2 - 1 + 2 = \left (2^{2^k} - 1 \right) \left (2^{2^k} + 1 \right) + 2 = F_n(F_n - 2) + 2 = F_0F_1 \cdots F_k + 2,

so it's also true for n = k + 1. n = k + 1.

Again, WLOG we assume that m > n . m > n. We have

gcd ( F m , F n ) = gcd ( F 0 F 1 F n 1 F n F n + 1 F m 1 + 2 , F n ) = gcd ( 2 , F n ) . \gcd(F_m, F_n) = \gcd(F_0F_1 \cdots F_{n - 1}F_nF_{n + 1} \cdots F_{m - 1} + 2, F_n) = \gcd(2, F_n).

However, F n F_n is always odd, so gcd ( 2 , F n ) = 1 , \gcd(2, F_n) = 1, and we are done. \blacksquare

The problem is a direct application of these two lemmas. WLOG let a > b . a > b. Applying Lemmas 1 and 2, we have

gcd ( 201 8 F a 1 , 201 8 F b 1 ) = 201 8 gcd ( F a , F b ) 1 = 201 8 1 1 = 2017 . \gcd(2018^{F_a} - 1, 2018^{F_b} - 1) = 2018^{\gcd(F_a, F_b)} - 1 = 2018^1 - 1 = \boxed{2017}.

In general, gcd ( n F a 1 , n F b 1 ) = n 1 \gcd(n^{F_a} - 1, n^{F_b} - 1) = n - 1 for all positive integers n n greater than 1.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...